Studi Analisis Motivasi Lulusan Pendidikan Vokasional Konstruksi Bangunan Universitas Negeri Jakarta Terhadap Bidang Kerja Non-Kependidikan (Konstruksi) - Fikri Kurniawan; Rosmawita Saleh; R. Eka Murtinugraha (Jurnal Pensil : Pendidikan Teknik Sipil, 2018)
AbstractThis study aims to obtain conception of motivation from graduates of Vocational Education of Building Construction in Faculty of Engineering, State University of Jakarta, to the non-educational work field (construction). It was conducted since Juni to July 2018.This study was conducted on graduates of bachelor degree of Vocational Education of Building Construction, Faculty of Engineering, State University of Jakarta. It uses descriptive method that is qualitative, the data retrieval technique is done by spreading the quistionnaire via google form to make it easier to get the quistionnaire answer.The result obtained from this study is that graduates of Vocational Education of Building Construction have high motivation to the non-educational work field (construction), they are motivatied by desires and ambitions (84%), impulses and needs (83%), hopes and aspirations (85%), exciting activities (84%), awards (80%), environmental influences that affect graduates to work in the non-educational work field (73%). It becomes the result that graduates of Vocational Education of Building Construction, Faculty of Engineering, State University of Jakarta, have a very high motivation to the non-educational work field (construction). Keywords: Graduates Motivation, Non-educational work field